Differential Release of Exocytosis Marker Dyes Indicates Stimulation-Dependent Regulation of Synaptic Activity - Henkel, Andreas W.; Mouihate, Abdeslam; Welzel, Oliver (Frontiers in Neuroscience, 2019)
There is a general consensus that synaptic vesicular release by a full collapse process is the primary machinery of synaptic transmission. However, competing view suggests that synaptic vesicular release operates via a kiss-and-run mechanism. By monitoring the release dynamics of a synaptic vesicular marker, FM1-43 from individual synapses in hippocampal neurons, we found evidence that the release of synaptic vesicle was delayed by several seconds after the start of field stimulation. This phenomenon was associated with modified opening kinetics of fusion pores. Detailed analysis revealed that some synapses were completely inactive for a few seconds after stimulation, despite immediate calcium influx. This delay in vesicular release was modulated by various stimulation protocols and different frequencies, indicating an activity-dependent regulation mechanism for neurotransmitter exocytosis. Staurosporine, a drug known to induce 'kiss-and-run' exocytosis, increased the proportion of delayed synapses as well as the delay duration, while fluoxetine acted contrarily. Besides being a serotonin reuptake inhibitor it directly enhanced vesicle mobilization and reduced synaptic fatigue. Exocytosis was never delayed, when it was monitored with pH-sensitive probes, synaptopHlourin and αSyt-CypHerE5 antibody, indicating an instantaneous formation of a fusion pore that allowed rapid equilibration of vesicular lumenal pH but prevented FM1-43 release because of its slow dissociation from the inner vesicular membrane. Our observations suggest that synapses operate via a sequential 'kiss-and-run' and 'full-collapse' exocytosis mechanism. The initially narrow vesicular pore allows the equilibration of intravesicular pH which then progresses towards full fusion, causing FM1-43 release.